Description Of Primary School Student Behavior Post The 21 Days Tooth Brushing Program (Survey Of Students At Sdn Bangetayu Wetan 01 Semarang City) - Putri, Salsabila Awalia; Amurwaningsih, Musri; Shafia, Arina (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: The high incidence of dental caries in elementary school-aged children was a public health problem. One effort to reduce the high rate of dental caries was through a 21-day tooth brushing program. It was hoped that the behavior would form permanently and become a habit. The purpose is to find out the description of elementary school students' behavior after the 21-day tooth brushing program.Method: The type of research was descriptive observational. The population in this study was elementary school students at SDN Bangetayu Wetan 01 Semarang City, totaling 386 students from grades 1 to 6. The sampling technique used was a total sampling technique which was in accordance with research inclusion and exclusion criteria, resulting in 105 samples. Data were subjected to descriptive statistical analysis.Result:The study showed that changes in dental and oral health maintenance behavior after the 21-day tooth brushing intervention were mostly in the sufficient category (49.5%). The majority of students' 21-day tooth brushing practice was in the routine category (82.9%). Conclusion: The most common characteristics of respondents were female (62.9%) and 10 years old (24.8%).Through the 21-day tooth brushing program, the students of SDN Bangetayu Wetan 01 Semarang City formed dental and oral health maintenance behavior.